Serum hypercoagulability states in Coats’ disease - Ghassemi F (Dove Medical Press, 2017)
Fariba Ghassemi,1 Carol L Shields,2 Masoumeh Mohebbi,1 Mehdi Nili Ahmadabadi,1 Fatemeh Morsali,1 Siamak Sabour3,4 1Ocular Oncology and Retina and Vitreous Service, Farabi Eye Hospital, Tehran University of Medical Sciences, Tehran, Iran; 2Ocular Oncology Service, Wills Eye Hospital, Thomas Jefferson University, Philadelphia, PA, USA; 3Safety Promotion and Injury Prevention Research Centre, 4Department of Clinical Epidemiology, School of Health, Shahid Beheshti University of Medical Sciences, Tehran, Iran Purpose: The purpose of this study was to investigate the serum hypercoagulability state and common viral and protozoan infections in Coats’ disease versus a normal control group. Materials and methods: In this comparative case series, 22 consecutive patients with Coats’ disease and 19 non-Coats’ patients undergoing lensectomy for congenital, traumatic, or senile cataract between January 2011 and June 2014 were included. Laboratory data for hypercoagulability states and common viral and protozoan infections were investigated. Results: The mean age for the Coats’ group was 14.5 years (median 8 years, range: 2 months to 59 years), and for the control group it was 30.6 years (median 17 years, range: 2–82 years). In patients aged 10 years or younger, anticytomegalovirus immunoglobulin G (IgG) (P≤0.01), homocysteine (P=0.03), and serum beta globulin (P<0.001) were associated with Coats’ disease. In those older than 10 years, higher serum protein S (P=0.04), beta globulin (P=0.05), and gamma globulin (P=0.04) were related to Coats’ diagnosis. After adjusting for sex and age as confounding factors, only beta globulin was found to be associated with Coats’ disease in logistic regression analysis (odds ratio: 1.8, 95% confidence interval: 1.0–3.1, P=0.02). Conclusion: Serum beta globulin levels appear to be elevated in patients with Coats’ disease. Keywords: anti-cytomegalovirus antibody, anti-herpes simplex antibody, Coats’ disease, blood hypercoagulability state, retinal telangiectasia, serum electrophoresis